Service traders in Hungary: Evidence from firm level data - Judit Rariga (Magyar Nemzeti Bank, 2017)
The aim of this paper is to present new empirical evidence on the characteristics of service trader firms using a novel dataset for Hungary. In the period of slowing growth of goods trade, services, which are more resilient to cycles and are growing steadily since the crisis, might open new alternatives for foreign trade expansion. By using firm level data for the period 2006-2014, this paper documents a series of stylized facts as follows. First, services exporters or goods and services exporters (bi-exporters) are even fewer than goods exporters, but they are present in almost all major sectors of the economy. Even manufacturing firms trade in services. Second, average yearly export values are higher for bi-exporters, both in services and goods. Third, services exporters outperform goods exporters in various dimensions: they are larger in terms of employment, give higher wages, have higher labor and total factor productivity. The effect of exporting slightly differs by industries and it is more pronounced for SMEs than for large companies. Service traders increase their productivity before starting to export and increase it further after entering foreign markets. Lastly, there is also some evidence on switching trader status. Earlier services exporter status is positively correlated with future services exporter status and bi-exporter status, indicating that firms might be willing to diversify their export portfolio in the goods-services dimension and not only along product/service type and destination country, as documented earlier. Most of the above findings prevail for importing as well.
Keywords: F14; F19; F23; 330; International trade; Services; Firm-level evidence